Hubungan Intensitas Mengakses Instagram Ajaib dan Daya Tarik Brand Ambassador Ajaib dengan Minat Menggunakan Ajaib sebagai Aplikasi Investasi Online - Krisanti Cahyaningtyas, Yulia; Setyabudi, Djoko; Manalu, S. Rouli (Interaksi Online, 2021)
The research aims to determine The Correlation between The Intensity of Accessing Ajaib's Instagram and The Attractiveness of Ajaib's Brand Ambassador with The Intention in Using Ajaib as Online Investment App. The results showed that the intensity of accessing Ajaib's Instagram with the intention in using Ajaib as online investment app has a significant value of 0.000 and a correlation coefficient value of 0.281, very significant, the strength of the relationship between variables is moderate, and positive level of correlation. The attractiveness of Ajaib’s brand ambassadors with the intention in using Ajaib as online investment app has a significant value of 0.038 and a correlation coefficient value of 0.154, significant, the strength of the relationship between variables is very weak, and positive level of correlation. The Theory of Reasoned Action and Source Attractiveness Model applies in research. The results of this study indicate the importance of social media in consumer buying and purchasing behavior, so it is necessary to pay attention to the quality of the content delivered. This research also helps to measure the success of brand ambassador appeal with interest in using the application.